A bibliometric analysis of collaboration skills in education (2019-2021) - Sri Marmoah; Rivan Gestiardi; Sarwanto Sarwanto; Chumdari Chumdari; Ika Maryani (Journal of Education and Learning (EduLearn), 2022)
One indicator of 21st century skills is collaboration; essential skill students must acquire in century learning. This study aimed to reveal research trends over the last three years based on the start of COVID-19 by using content analysis and reviewing bibliometric results related to articles with collaboration keywords. For bibliometric mapping analysis, a total of 500 articles were accessed, and for content analysis, 31 articles were selected between 2019-2021 based on Google Scholar's database corresponding to the education field study of the research. The results showed that digital "health education collaboration" was the most searched keyword, while researchers focused on collaboration in education between 2019-2021. The most commonly used words in abstracts are teaching, creativity, ability, and community. It was evident that the latest articles primarily focused on skills. Bhone Myint Kyaw; AE Kinio is the most cited author in this field. The most cited journals are the Journal of Medical Internet Research, Journal of Surgical Education, The Journal of Technology Transfer, the most prominent journal. The content analysis results showed that "21st-century skill, problem, and implementation" has become the most studied variable in the article.